Accounting for Managers Interpreting Accounting Information for Decision Making, 4th Edition - Collier, Paul (John Wiley & Sons, 2012)
Updated and revised, the new fourth edition of Accounting for Managers builds on the international success of the previous editions in explaining how accounting is used by non-financial managers. Emphasizing the interpretation rather than the construction of accounting information, Accounting for Managers encourages a critical, rather than an unthinking acceptance of accounting techniques. Whilst immensely valuable for planning, decision-making and control, users of accounting information need to recognize the assumptions behind, and the limitations of particular accounting techniques. As in the previous editions, Accounting for Managers links theory with practical examples and case studies drawn from real business situations across a wide range of manufacturing, retail and service industries.
Previous edition: 2009. - Includes bibliographical references and index
Keywords: Managerial accounting; Comptabilité de gestion